2018
DOI: 10.1200/jgo.17.00081
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Histology Turnaround Time Through Stepwise Innovation and Capacity Building in Rwanda

Abstract: PurposeMinimal turnaround time for pathology results is crucial for highest-quality patient care in all settings, especially in low- and middle-income countries, where rural populations may have limited access to health care.MethodsWe retrospectively determined the turnaround times (TATs) for anatomic pathology specimens, comparing three different modes of operation that occurred throughout the development and implementation of our pathology laboratory at the Butaro Cancer Center of Excellence in Rwanda. Befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…23 However, a study from Rwanda showed a median pathology TAT of two weeks utilizing telepathology services, suggesting telepathology may be an important tool in decreasing pathology TAT and overall time to diagnosis in resource limited settings. 24 There is little uniformity in the association of factors influencing diagnostic delays in LMICs in the literature, suggesting varying impact of age, sex, distance to a pediatric cancer center, type of cancer, and metastasis on time to diagnosis. For example, studies in Nigeria, South Africa, Brazil, and now our study suggest that the age of the child does not significantly affect time to diagnosis, which differs from studies in Peru, Turkey, Egypt, Indonesia, and Mexico [9][10][11][12]14,15,17,25 (Supporting Information Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 However, a study from Rwanda showed a median pathology TAT of two weeks utilizing telepathology services, suggesting telepathology may be an important tool in decreasing pathology TAT and overall time to diagnosis in resource limited settings. 24 There is little uniformity in the association of factors influencing diagnostic delays in LMICs in the literature, suggesting varying impact of age, sex, distance to a pediatric cancer center, type of cancer, and metastasis on time to diagnosis. For example, studies in Nigeria, South Africa, Brazil, and now our study suggest that the age of the child does not significantly affect time to diagnosis, which differs from studies in Peru, Turkey, Egypt, Indonesia, and Mexico [9][10][11][12]14,15,17,25 (Supporting Information Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Although there are limited pathology TAT data from LMICs in the literature, one study in Malawi showed a median pathology TAT of 10.1 weeks . However, a study from Rwanda showed a median pathology TAT of two weeks utilizing telepathology services, suggesting telepathology may be an important tool in decreasing pathology TAT and overall time to diagnosis in resource limited settings …”
Section: Discussionmentioning
confidence: 99%
“…A total of 3,514 samples were analyzed in total. The study carried out by Muvugabigwi et al (9) discovered that TAT was significantly shortened for tissue biopsies uploaded to the iPath case sharing platform. Sending the blocks and slides to BWH resulted in a median TAT of 30 days while the iPath platform's median TAT was 14 days.…”
Section: Role Of Telepathology In Low Resource Settingsmentioning
confidence: 99%
“…Significant capital outlay is also required for the purchase of the necessary bandwidth as well as cloud storage space. This is far beyond the entire budget of most public/private laboratories in underdeveloped countries.Cheaper alternatives involving transfer of static slide images have evolved, and successes have been reported in the achievement of concordance between diagnoses made on slide images when compared with diagnoses made on glass slides (9). The drawback to static image transfer as earlier stated includes its lack of control of magnification and focus by the pathologist receiving the images.…”
Section: Challengesmentioning
confidence: 99%
“…In Rwanda, when the cancer centre was set up in Butaro in 2012, where slides were prepared and sent to Boston, the median TAT was 30 days. Static image telepathology reduced that to 14 days, but the use of visiting pathologists reduced this to 5 days [10]. A clear lesson from both these examples is the major benefits of having on-site pathologists.…”
Section: Standardsmentioning
confidence: 99%